Demarcation of ethics and law: a theoretical framework that recaptures the primary role of akhlāq Islamiyyah - Awang Abd Rahman, Amilah (Islamic Cultural Centre, 2018)
This paper revisits the role of Islamic ethics (akhlāq islamiyyah). The author argues that Islamic ethics has, so far, not been appropriately treated as a full-fledged discipline and is very much overshadowed by the discipline of law. Thus, the discussion focuses on major features which distinguishing Shari‘ah law from akhlāq comprising the principal tasks, goals and orientation, affecting other supporting concepts of sanction, nature of judgement and action. This modest attempt delineates the comprehensive role of Islamic ethics as a major contribution to mankind’s well-being, one that also offers a more balanced view of religion. The study finds that both law and akhlāq fundamentally diverge and only by functioning as two different domains, can they complement each other and potentially balance the dynamics of self-development and social intercourse. Akhlāq therefore, is not depicted as a dry discipline of regulations but rather as a system of liberation that obtains excellence and an individually optimized state of self-governance that achieves success in this life and the next, without which the real meaning of philosophy of the religion, namely Islam, will not be grasped.